The Use of 16S rRNA and nodC Gene Sequence in Resolving The Phylogenetic Relationship of Rhizobia Associated With Paraserianthes falcataria (L.) Nielsen Plant - Prana, Titik K; Sone, Teruo; Kawasaki-Nakagawa, Hiroko; Yokota, Atsushi; Seki, Tatsuji; Tomita, Fusao (Annales Bogorienses, 2004)
Studies on genetic position of several isolates living symbiotically on Paraserianthes falcataria have been carried out using amplification and sequencing techniques of 16S rDNA and specific gene for nodulation. The phylogenetic tree constructed based on 16S rDNA showed that rhizobia growing symbiotically on Paraserianthes falcataria consisted of 3 groups. The first group, was fast growing rhIzobia which have close relationship to Rhizobium tropicii, the second and the third groups were slow-growing rhizobia which have close relationship to Bradyrhizobium elkanii and Bradyrhizobium japonicum. However, the phylogenetic tree constructed on the basis of partial nodC gene indicated the existence of an independent group, since they did not show any significant degree of relationship with the existing groups. This was also supported by differences in physiological characteristic i.e Indole Acetic Acid production and salt tolerance of the isolates. These differences shows us that direct sequencing method of certain specific genes could give a more specific result than would display more clearly the degree of relationship at species level.